Google Search Volume And Investors’ Decision On Return And Liquidity In Indonesia - Fauzi, Fauzi; Santi, Faurani; Anuar, Sanusi; Citrawati, Jatiningrum (Opción, 2019)
This research investigates whether investors’ attention measured by Google Search Volume, has any impact over the stock ’s return and liquidity. The Fama French three factor model is used to test the relationship between investors’attention and the stock ’s return. This research found that Google Search Volume primarily captures the attention of investors, resulting in a short-term buying pressure that creates a higher return. In conclusion, an increase in Google Search Volume fails to reduce information asymmetry that leads to an increase in liquidity.